KECERDASAN SPIRITUAL BAGI KEHIDUPAN ORANG KRISTEN MASA KINI : SUATU KAJIAN BIBLIKA - Supriadi Oet; Romauli Rinawati Hutabarat (Sekolah Tinggi Teologi Arastamar Bengkulu, 2025)
This article explores the importance of spiritual intelligence in the life of Christians in the modern era. Spiritual intelligence, which includes self-awareness, the meaning of life, and the relationship with God, has an important role in guiding individuals through life's challenges and giving deeper meaning to their existence. In the context of an increasingly complex and materialistic society, spiritual intelligence helps Christians to live with integrity, live the teachings of Christ, and strengthen their relationships with God and others. This article highlights various aspects of spiritual intelligence and how its application can improve the quality of life, provide inner peace, and build a strong and harmonious faith community. This research also underlines the importance of education and self-reflection in developing true spiritual intelligence. The crisis of spiritual identity due to the dominance of materialistic values and moral relativism as well as the lack of understanding of the concept of spiritual intelligence (SQ) in the context of Christianity. Through qualitative research methods, the author gives a persuasive exposition in finding the important role of spiritual intelligence for the lives of Christians today. Without neglecting the presence of intellectual and emotional intelligence. This writing provides an understanding of Spiritual intelligence as a major contribution to intellectual and emotional intelligence in the lives of today's Christians. The ultimate goal of writing is not only as an information about spiritual intelligence. But it is more to direct the right perspective so that today's Christians can maximise spiritual intelligence in today's life.